2020
DOI: 10.1103/physrevlett.125.107002
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Superconducting Transition by Rotation of an Inversion Symmetry-Breaking Axis

Abstract: We consider a hybrid structure where a material with Rashba-like spin-orbit coupling is proximity coupled to a conventional superconductor. We find that the superconducting critical temperature T c can be tuned by rotating the vector n characterizing the axis of broken inversion symmetry. This is explained by a leakage of s-wave singlet Cooper pairs out of the superconducting region, and by conversion of s-wave singlets into other types of correlations, among these s-wave odd-frequency pairs robust to impurity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…On the theory side, the vortex surface barriers and corresponding critical currents should be evaluated numerically for various superconducting hybrids of interest [27,78,79], for example using the quasiclassical Green's function method [80] or Bogoliubov-de Gennes equation [1]. The recent new insights regarding orbital contributions to magnetization in superconductors with Rashba SOC [81] pose another important question and could offer an avenue for enhancement of the critical current modulation.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…On the theory side, the vortex surface barriers and corresponding critical currents should be evaluated numerically for various superconducting hybrids of interest [27,78,79], for example using the quasiclassical Green's function method [80] or Bogoliubov-de Gennes equation [1]. The recent new insights regarding orbital contributions to magnetization in superconductors with Rashba SOC [81] pose another important question and could offer an avenue for enhancement of the critical current modulation.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Our binomial search algorithm for the superconducting critical temperature, is the same as the one we have previously presented in Ref. [18], and we only summarize the main steps here. We divide the temperature interval 𝑁 𝑇 times.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Previous studies have suggested introducing heavy-metal layers boosting the interfacial Rashba spin-orbit coupling in a S/F bilayer [11][12][13][14][15][16][17]. The Rashba spin-orbit field introduces additional symmetry breaking [18] that allows for control over the spin-triplet channels when rotating the magnetization of the single ferromagnetic layer. However, for a structure with purely Rashba spin-orbit coupling, a variation in the triplet generation for in-plane rotations of the magnetization is only possible in ballistic-limit systems [15], while additional Dresselhaus spin-orbit coupling is needed for such an in-plane effect in the diffusive limit [11].…”
mentioning
confidence: 99%
“…In this setup, the interface normal is parallel to the x axis, meaning spatial inversion symmetry is broken along x. The SF bilayer converts even-frequency s-wave singlets into evenfrequency p x -wave triplets and odd-frequency s-wave triplets [56]. The latter do not contribute to the T c enhancement discussed here.…”
mentioning
confidence: 99%